Analysis of Career Potential Based on Holland's Theory to Prepare Graduates among Students with Intellectual Disabilities - Peby Tri Hartati; Hermanto Hermanto (STAI Hubbulwathan Duri, 2024)
Students with intellectual disabilities often encounter significant challenges as they prepare for post-graduation careers. Recognizing the importance of aligning career paths with individual interests and abilities, SLB Negeri 1 Yogyakarta serves as a pivotal institution in vocational education for these students. This research employs case studies to delve into the ways vocational education programs can enhance career readiness among intellectually disabled students, using interest and talent assessments based on Holland’s theory. The study involves 28 students at the SMALB level, a guidance counselor, 10 vocational instructors, and 8 parents, employing methods such as semi-structured interviews, participatory observations, and documentation analysis. Findings indicate a significant correlation between Holland's personality types and the career interests of students, with realistic, conventional, and artistic types prevailing. Moreover, career guidance grounded in Holland's theory at SLB Negeri 1 Yogyakarta effectively nurtures vocational skills that resonate with the students’ talents and capabilities, supporting their potential career trajectories.